’In yaqum vs ’in qāma: un'ipotesi modale - Manuela E. B. Giolfo (Kervan. International Journal of Afro-Asiatic Studies, 2006)
This paper considers all systems of conditional structures of the type ’in šarṭ jawāb al-šarṭ as treated by main Arab scholars. It investigates the opposition between yaqum vs qāma forms as a reason for including/excluding some verbal structures in/from the conditional system of each considered grammarian. An assumption is made that the frontier between yaqum vs qāma verbal forms in the conditional context can be interpreted in terms of the opposition between the two Aristotelian modal categories of “possibility” and “necessity”. The hypothesis is tested on the occurrences of ’in šarṭ jawāb al-šarṭ structures in the Koran. A formalization of conditional systems by means of standard modal logic  S4 is then given and discussed.